ESTABLISHING AND SIGNIFICANCE OF THE THEOLOGY IN PRIZREN FOR THE PRESERVATION OF SERBIAN NATIONAL SPIRIT IN THE TERRITORY OF OLD SERBIA (Heritage, 2021)
The Seminary in Prizren, in addition to enabling the authorities from Belgrade to be present in the Ottoman Empire, was a center of cultural and educational development. The day it was founded seems like the day the struggle for liberation began, liberation of the Serbian population. She worker to preserve and raise national conscience among people in Old Serbia and Macedonia, who lived under various pressures from Turks, Bulgarians and Albanians.From its inception until today, the Seminary has been a cultural and educational nursery for Serbs. It represented the motherland of all schools that existed in that period in Old Serbia.  It sought to help, not only individuals, also she has already advocated for the opening of new schools and the spread of literacy, as well as the survival od Serbian politics in these area. All the efforts of the Seminary to spread Serbian culture, tradition and religion would not have been successful without the Russian consulate, and especially the Russian consul Ivan Sthepanovic Jastrebov, then its founder and benefactor Simo Andrejevic Igumanov, but also all its menagers who have changed over the years, and exposed to enormous risks in order to preserve this school and its significance for the Serbian people. The rectors and teachers of the school were seen by the Turks as spies who passed everything on to the authorities in Belgrade, so they were constantly interrogated, the school was searched, books that the Turkish authorities considered unsuitable were confiscater and destroyed, and the school and rooms where students and teachers slept was repeatedly searched. The school was a great responsibility for the they leaders, because they did not allow it to be closed, because at that time it was the only support for the Serbian people.
Keywords: Seminary in Prizren, Old Serbia, culture, tradition, education, Orthodoxy, politics, school